Affective Worldmaking Narrative Counterpublics of Gender and Sexuality - Schultermandl, Silvia; Aresin, Jana; Pages Whybrew, Si Sophie; Simic, Dijana (Edition Medienwissenschaft, 2022)
What makes up a public, what governs dominant discourses, and in which ways can counterpublics be created through narrative? This edited collection brings together essays on affect and narrative theory with a focus on the topics of gender and sexuality. It explores the power of narrative in literature, film, art, performance, and mass media, the construction of subjectivities of gender and sexuality, and the role of affect in times of crisis. By combining theoretical, literary, and analytical texts, the contributors offer methodological impulses and reflect on the possibilities and limitations of affect theory in cultural studies.